A feeder link planning method for total supply capability improvement of distribution network - Xiao, Jun; Lv, Zihan; Zu, Guoqiang; Song, Chenhui (Frontiers in Energy Research, 2022)
This paper proposes a new feeder link planning method for the distribution network, which can improve total supply capability (TSC). Feeder links are the key component of distribution networks. They are of great significance on TSC of the distribution network. Therefore, it is necessary to reveal the influence rules of feeder links on TSC then apply the rules in distribution network planning. Firstly, the indices describing the position, scale and efficiency of feeder links are defined. Secondly, the influence rules of feeder links on TSC are revealed. (1) The more balanced the feeder geometrical distribution is, the higher TSC is. (2) The larger the feeder link scale is, the higher TSC is. While, for both (1) and (2), the TSC will remain unchanged after reaching a certain value. (3) There always exists an optimal construction order of feeder links which can ensure the TSC as high as possible in each planning stage. Thirdly, based on the rules, a model and an algorithm of the feeder links planning are proposed. The method can find an optimal construction order of feeder links, which can ensure the value of TSC as high as possible in each feeder link planning stage. Finally, the proposed method is verified on an 8-substation-transformers case grid, which has shown the proposed method has advantages in the aspect of feeder link efficiency, feeder-distribution balancing, especially the TSC can be improved in each planning stage than the traditional method.